2020
DOI: 10.3390/medicina56090441
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Bladder Cancer in Type 2 Diabetes Mellitus Patients: A Population-Based Cohort Study

Abstract: Background and objectives: Type 2 diabetes mellitus (T2DM) is becoming increasingly prevalent worldwide and is associated with increased incidence of kidney cancer and bladder cancer (BC). However, studies have produced conflicting results. Therefore, we retrospectively evaluated the incidence of BC in T2DM patients using the Taiwan National Health Insurance Research Database (NHIRD). Materials and Methods: We included 31,932 patients with a diagnosis of T2DM in the study group and 63,864 age- and sex-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Padureanu et al described a case of a 20-year-old patient, with complaints of hematuria, dysuria, and colicky pain, which were later found to be the caused by the urological manifestation of tuberous sclerosis complex (TSC) [35]. Pan et al assessed the incidence of bladder cancer in patients with Type 2 diabetes mellitus (T2DM) in a study population of 31,932 T2DM patients, compared to the control group of 63,864 patients without diabetes: overall, they have found that T2DM patients do not have a higher risk of developing bladder cancer [36]. Lee et al studied the potential anticancer properties of epigallocatechin gallate (EGCG) on a human urinary bladder transitional cell carcinoma (TCC) cell line; during the analyses, the expression profiles of mRNAs and microRNAs were analyzed using next-generation sequencing (NGS) and bioinformatics.…”
mentioning
confidence: 99%
“…Padureanu et al described a case of a 20-year-old patient, with complaints of hematuria, dysuria, and colicky pain, which were later found to be the caused by the urological manifestation of tuberous sclerosis complex (TSC) [35]. Pan et al assessed the incidence of bladder cancer in patients with Type 2 diabetes mellitus (T2DM) in a study population of 31,932 T2DM patients, compared to the control group of 63,864 patients without diabetes: overall, they have found that T2DM patients do not have a higher risk of developing bladder cancer [36]. Lee et al studied the potential anticancer properties of epigallocatechin gallate (EGCG) on a human urinary bladder transitional cell carcinoma (TCC) cell line; during the analyses, the expression profiles of mRNAs and microRNAs were analyzed using next-generation sequencing (NGS) and bioinformatics.…”
mentioning
confidence: 99%
“…DM was also a risk factor for bladder cancer. It was associated with cancer incidence and poor prognosis [23][24][25]. In the present study, bladder cancer patients with DM who were ever-smokers had a multiplier effect, which significantly increased the overall and specific mortality rates.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 60%
“…Regarding women, the correlation between smoking and mortality will need to be investigated further in the future. Last, all patients were treated in the Taiwanese medical system, indicating a potential lack of generalizability, although some studies have confirmed the accuracy of the information in Taiwan’s National Health Insurance Research Database [ 35 ], and some topics which were discussed in our study have been published internationally, such as bladder cancer [ 36 ] and smoking [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The UK biobank observed stronger associations in women, and also found positive associations with T2DM medication and longer duration, and with glycated hemoglobin levels [ 25 ]. Regarding cohort studies of diabetics, a Taiwanese cohort study [ 27 ] of diabetic patients found no association (without adjusting for important bladder cancer risk factors such as smoking), whereas a Korean study reported positive associations with T2DM after multivariable adjustment for confounders, and also with T2DM duration and impaired fasting glucose [ 28 ]. An Italian study [ 7 ] also found a positive association with bladder cancer in T2DM patients, but they only adjusted for age and sex.…”
Section: Discussionmentioning
confidence: 99%